CBVT analysis of canal configuration of the mesio-buccal root of maxillary first permanent molar teeth: An in vitro study - R Pratima Shenoi; Hrishikesh M Ghule (Wolters Kluwer Medknow Publications, 2012)
Context: For successful endodontic treatment, it's imperative to locate and obturate all root canals. As concluded by Ingle, the major cause for failure of root canal therapy is in ability to recognize all theexisting canals and subsequent failure in their obturation. Aim: To analyze the canal configuration of the mesio-buccal root of maxillary first permanent molar teeth. Materials and Methods: A total of 30 recently extracted human permanent maxillary first molars were collected and stored in a container with 5% Sodium Chloride solution for four days. Teeth with open apices, external resorption, improperly formed roots and teeth with previous restorations were excluded. Using the dental modeling wax, teeth were arranged in a 'U' shaped arch with roots embedded inside the wax and occlusal surface remaining free. 10 teeth were arranged in each arch and three such sample plates were prepared. Flat surface of the base encasing enabled the plate to be mounted on ﬂat plastic bite plate. With bite plate roughly centered in the focal trough area Axial, Coronal and Sagittal section Cone-Beam Computed Tomography (CBCT) images were taken with Kodak 9000 Extra-oral Imaging System. Images displayed on a monitor were inspected by two endodontists using Kodak Dental Imaging Software 3D Module V2.2. Statistical Analysis: When the data was observed, it was found that 24 teeth out of total 30 teeth examined showed some variation (i.e. possible additional canal) along the length of the mesio-buccal root canal. Out of these 24 teeth, 13 showed presence of additional canal at coronal third, 7 showed presence of additional canal at middle third and four showed presence of additional canal in apical third level. Percentage analysis was done as there was no group comparison to be done. Results: Cone-Beam Volumetric Tomography (CBVT) evaluation positively identiﬁed the variations in mesio-buccal canal in 80% of samples. Out of these, 54.16% were in coronal 3 rd, 29.16% in middle 3 rd and 16.66% were in apical 3 rd . Conclusion: Within the limitations of this study, it can be concluded that- (1) more than half of maxillary ﬁrst molars have four canals and (2) most of the additional canals were located in the MBR and CBVT is a good diagnostic tool to help diagnose these additional canals. Further investigations using larger sample sizes would be helpful.